Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00198-015-3265-0
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density for age/osteoporosis in triple A syndrome—an overlooked symptom of unexplained etiology

Abstract: Low BMD for age/osteoporosis in our patients probably is not a result of glucocorticoid therapy but could be the consequence of low level of adrenal androgens, neurological impairment causing physical inactivity, inadequate sun exposure, and protein malnutrition secondary to achalasia. Considering ubiquitous ALADIN expression, low BMD/osteoporosis may be a primary phenotypic feature of the disease. Besides optimizing glucocorticoid dose, physical activity, adequate sun exposure, appropriate nutrition, and vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Osteoporosis, confirmed by measurement of low bone density, and presenting as early as childhood, has been reported in sporadic cases 48,49. It has been suggested that steroid supplementation alone could not explain the finding.…”
Section: Endocrinementioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis, confirmed by measurement of low bone density, and presenting as early as childhood, has been reported in sporadic cases 48,49. It has been suggested that steroid supplementation alone could not explain the finding.…”
Section: Endocrinementioning
confidence: 99%
“…It has been suggested that steroid supplementation alone could not explain the finding. The cause may be multifactorial, given decreased or lack of physical activity and sun exposure due to immobilization in progressive neurological disease, malnutrition secondary to achalasia, and low levels of androgens 48. As such, patients and families should be counseled on preventive measures, screening, and nutritional supplementation.…”
Section: Endocrinementioning
confidence: 99%
“…Upstream binding transcription factor ( UBTF ) functions in ribosomal RNA (rRNA) polymerase (Pol I and II)-specific transcription of the ribosomal genes to maintain genome stability, and the inhibition of UBTF leads to DNA damage and genomic instability independent of Pol I transcription [40], Bone cell proliferation and differentiation could be regulated by suppressed rRNA gene transcription due to UBTF acetylation modulated by RUNX2–HDAC1 interaction [41]. The mutation of Aladin WD repeat nucleoporin ( AAAS ) gene causes Triple A syndrome (alacrima, achalasia, adrenal failure, progressive neurodegenerative disease), which leads to osteoporosis due to reduced generation of testosterone and estrogens by adrenal androgens, less physical activity, and decreased exposure to the sun [42]. Meanwhile, our study found that AAAS, nucleoporin 155 (NUP155) , and Cvclin B1 (CCNB1) were significantly enriched in the GO term of mitotic nuclear envelope disassembly and directly interacted with the hub genes of the biological network (Fig.2C).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical background of ACTH-independent and -dependent CS differs with regard to adrenal androgens [ 3 ]. Endogenous adrenal androgen is associated with the activation of osteoblasts or bone turnover [ 7 , 8 ]. The osteoporosis seen in adrenal CS has been speculated to be more influenced by CE, especially in women.…”
Section: Introductionmentioning
confidence: 99%